Tools for measuring the full impacts of agricultural interventions - Martin, Will (International Food Policy Research Institute, 2021)
A first step in evaluating the effects of agricultural investments in developing countries to recognize that makers will almost certainly have multiple objectives. Even makers like those at the Millennium Challenge Corporation, with a strong focus on ensuring that interventions contribute to growth, also have a keen interest in poverty reduction and other goals such as enhancing gender equity. This presence of multiple goals has profound impacts on the choice of policies and mean it is likely that more than one instrument will be needed to best achieve those goals. Once the goals of have been identified, the next step is to identify possible instruments to help in achieving these goals. These potential instruments will likely include some reforms like adjustments to trade policies that are relatively easy to implement, whose impacts are relatively easy to analyze and whose implications for fiscal revenues may be slight. They may also include re-forms to the ways that policies are identified and implemented, such as moves from centralized making to community driven development, designed to align policies more strongly with needs in the communities affected. They are also likely to include investment projects with substantial revenue requirements that seek to rectify market failures in areas such as the provision of public goods or the internalization of externalities. Constraints Analyses are an important part of the MCC approach to identifying and evaluating interventions using the Hausmann, Rodrik and Velasco growth diagnostic approach (HRV). This seeks to identify areas in which substantial progress can be made at limited cost by identifying key omissions in cur-rent policies. Their famous, and useful, analogy to a barrel with a short stave whose lengthening can increase the water level in the barrel at minimum cost helps grasp the essence of this approach. It deals with situations where inefficiencies in past making, and/or changes in circumstances mean that disproportionately large benefits are obtainable at low cost.